MESIN PENGERING KERUPUK HEMAT ENERGI TINTUK MENINGKATKAI PRODUKTIVIAS PRODIISEN KERUPUK - -, Sudiyatno -; S, Suprapto Rachmad (Universitas Negeri Yogyakarta, 2004)
The objectiveofproducinga low energydrying machineistohelpchipsindustriesin increasingtheirproductivifybyshorteningthe dryingtime. Up tonowtheyuse heat of sunlight to drythechips.Thisprocessis rime consumingarrdwhy the dry seasoncolnes,theprocess isdelayed.It decreases thequalityof chips. fhe drying machineproduceduses firewoodplacedin a furnaceas theheat source.Theheatis then flown throughpipesintothedrying room, where wetchips areplaced. ,,;Theroomhasalengthof 1.2 m, a heightofI m and a widthot-I m. Ithas twodoors and equippedwith a thermometer. Below the room,there is a furnace havingcapacitycf6 kg f-rre woodandan oxygeninlet. The drying temperatureis 60 I kg firewoodcanproducetheheat withtemperatureof60-70oC for1.5hours.Thedryingprocessof wetchips takes about 5 hours,For that of halfdrychips, it takes2hours. Thismachinehas capacify of2.400rvetchips and 6.000halfdrychips.